2023
DOI: 10.3390/ma16145123
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Velocity and Attenuation of Low-Carbon Steel at High Temperatures

Jan Lean Tai,
Mohamed Thariq Hameed Sultan,
Andrzej Łukaszewicz
et al.

Abstract: On-stream inspections are the most appropriate method for routine inspections during plant operation without undergoing production downtime. Ultrasonic inspection, one of the on-stream inspection methods, faces challenges when performed at high temperatures exceeding the recommended 52 °C. This study aims to determine the ultrasonic velocity and attenuation with known material grade, thickness, and temperatures by comparing theoretical calculation and experimentation, with temperatures ranging between 30 °C to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Previous research has shown that ultrasonic wave parameters (attenuation) can accurately be used to detect the physical properties of materials. Measuring turbine steam exhaust wetness (Zhu et al, 2023), particle size distribution of carbonyl iron powder (Wei et al, 2023), determine the material level, thickness, and temperature of carbon steel materials (Tai et al, 2023), measuring the surface roughness of materials (H. Liu et al, 2023), material measurement aluminum alloy 2219-O (S. Li et al, 2023), cavity content and density of polyester filaments (K. Liu et al, 2017), testing the porosity of composite laminates (Z. Li et al, 2014), detect Escherichia coli bacteria (Ravinder Reddy et al, 2001), metal-polymer composites (Hidayat et al, 2020) and detect contamination in the material (Bhagaspati et al, 2021;Khairurrahman et al, 2021;Salsabila et al, 2021).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Previous research has shown that ultrasonic wave parameters (attenuation) can accurately be used to detect the physical properties of materials. Measuring turbine steam exhaust wetness (Zhu et al, 2023), particle size distribution of carbonyl iron powder (Wei et al, 2023), determine the material level, thickness, and temperature of carbon steel materials (Tai et al, 2023), measuring the surface roughness of materials (H. Liu et al, 2023), material measurement aluminum alloy 2219-O (S. Li et al, 2023), cavity content and density of polyester filaments (K. Liu et al, 2017), testing the porosity of composite laminates (Z. Li et al, 2014), detect Escherichia coli bacteria (Ravinder Reddy et al, 2001), metal-polymer composites (Hidayat et al, 2020) and detect contamination in the material (Bhagaspati et al, 2021;Khairurrahman et al, 2021;Salsabila et al, 2021).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Its superiority over UT is evident in its multiple-element probe, which permits flexible beam steering, rendering superior scan coverage and speed [65,66]. The proficiency of PAUT is reflected in its ability to provide threedimensional defect information through S-scan, C-scan, D-scan, and A-scan data, as shown in Figure 2 [67,68]. Comparative studies have affirmed the advantages of PAUT over traditional UT.…”
Section: Phased Array Corrosion Mapping Applicationmentioning
confidence: 99%